The Genetics and Clinical Presentation of Retinitis Pigmentosa A Tertiary Care Hospital Study - Muhammad Junaid Sethi, Umer Khan, Natasha Junaid, Nazli Gul, Ishan Ullah, Muhammad Israr, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: This study aims to analyze the retinitis pigmentosa patients' Clinical Presentation and inheritance patterns. Research conducted at the tertiary care hospital Material and methods: this tertiary care hospital study was carried out at a level I trauma center between 05 January 2018 to 05 January 2021. fifty-six patients and members of their families underwent an ophthalmic evaluation to help identify those with the condition and define its phenotype. The family tree was traced. Several relatives also had optical gheremco tomography and fundus photography. Results: at Presentation, 52 eyes (47%) were judged to be legally blind, whereas 38 (32%) had some degree of visual impairment. The visual field was narrowed in 22 instances ( 40%) due to the brightness of the interaction. In terms of inheritance patterns, we discovered that three cases were autosomal dominant (4%), 39 cases were autosomal recessive (70%), and three cases were x-linked (6%). Of the total cases, 11 (20%) were isolated incidents. There were 48 patients with a conventional retinitis pigmentosa image (86%) and eight patients with an unusual RP picture (12%), including three instances of pericentric RP (5%), 3 cases of Usher's disease (4%) and 1 case of retinitis punctata albescence (2%) bardet-biedl were identified in a single patient. Conclusions: Retinitis Pigmentosa Patients Have A Very Significant Risk Of Becoming Blind. Autosomal Recessive sporadically follows the Most Prevalent Pattern Of Inheritance. Early Detection Of Retinitis Pigmentosa Is Important In Preventing Blindness From The Disease, As Is Encouraging Patients To Forego Marriages To First Cousins. Keywords: Genetics and Clinical, Presentation, Retinitis Pigmentosa, kpc